DEVELOPMENT OF A FAULT DETECTION ALGORITHM BASED ON ELECTRICAL DRIVE RELIABILITY - Usmonov, Shukurillo Yulbarsovich (Educational Research in Universal Sciences, 2023)
The scientific significance of the research results is based on theoretical researches in the field of energy resources use, the regulation of the work processes of textile enterprise machines, modern automatic control theory methods and economical operation modes specific to electric machines, mathematical modeling through artificial neural networks, determining the energy consumption of electric machines, increasing the energy efficiency of the control system. It is explained by the research of the model and the method of increasing the new reliability.